Comparative mandible geometric morphometrics of two African rodents,Thryonomys swinderianus and Cricetomys gambianus (Rodentia: Thryonomyidae and Nesomyidae) - Samuel, O.M. (2016)
The African giant pouched rat (Cricetomys gambianus) and greater cane rat or African cane rat (Thryonomys swinderianus) both have similar body conformation and share similar ecological biome. This study aimed to compare mandibular parameters in adults of both species. For this purpose, 9 lateral mandibular landmarks in male T. swinderianus (n=11) and C. gambianus (n=12) were analyzed by geometric morphometrics. T. swinderianus presented a coronoid process equivalent to condyle and a more caudally displaced angular process, whereas cheek teeth was less prominent and shorter in C. gambianus. This study may be useful in solving phylogenetic ambiguities, wildlife surveillance and age-population control, ration formulation in captive species, and eco-migration. This is the first time to our knowledge that geometric morphometric comparison of mandibles in these African rodents has enabled an inference of ecological preferences in diet based on mandible shape.